A development-focused allocation of the special drawing rights - Ernest Aryeetey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
Efforts to realize the issue of development-focused Special Drawing Rights (SDR) by the International Monetary Fund (IMF) have been on-going for many years. Recently, however, the campaign first gained a new momentum immediately after the Asian financial crises with the new liquidity problems of developing nations following the collapse of private capital markets. Currently the search for financing options towards the achievement of the Millennium Development Goals drives the interest in development-focused SDRs. Extending the uses to which SDR can be put is derived from the growing demands on the international financial system to respond to the development finance needs of poor nations. Apart from the need to provide emergency funds in times of crises and the whole area of crisis prevention, increasingly the facilitation of development in poor countries and assistance to make the best policy decisions is considered crucial.
Keywords: F02; F33; F34; F35; O16; O19; O50; P16; H41; 330; Special Drawing Rights; international monetary arrangements; global public goods; global development finance; innovative finance; Millennium Development Goals; Sonderziehungsrechte; Internationales Währungssystem; Internationale Kreditvergabe; Entwicklungshilfe; Internationaler Finanzmarkt; Entwicklungsländer